Assessing allergenicity of different tomato ecotypes by using pooled sera of allergic subjects: identification of the main allergens - Bencivenni, Mariangela; Faccini, Andrea; Bottesini, Chiara; Rao, Rosa; Detoraki, Aikaterini; Ridolo, Erminia; Marone, Gianni; Dall’Aglio, Pier Paolo; Dossena, Arnaldo; Marchelli, Rosangela; Sforza, Stefano (European food research & technology, 2012)
An evaluation of the potential allergenicity of different tomato ecotypes is reported. Twelve tomato ecotypes were assessed through a proteomic approach, using pools of sera of allergic patients from two different regions (Emilia Romagna in Northern Italy and Campania in Southern Italy), in order to identify the major allergens and evaluate differences in IgE binding properties of the tomato cultivars. Pooled sera of allergic people from Emilia Romagna showed as the main allergen a suberization-associated anionic peroxidase, whereas pooled sera of allergic patients from Campania were mostly reactive to profilin. The two proteins were identified through a proteomic approach based on the use of high-resolution mass spectrometric techniques. Quite interestingly, in some cases, several ecotypes showed a less reactivity toward patients’ sera than other, potentially indicating the possibility to identify ipoallergenic varieties. Anyway, the allergenic pattern response to tomatoes was serum-specific, indicating that the allergenic properties of different tomato ecotypes are defined by the specific proteins to which the patient is sensitized, a strong indication that ipoallergenicity of the different ecotypes is possible, but mostly related to the individual susceptibility.